Drought vulnerability modeling over Mandawa watershed, northern Iraq, using GIS-AHP techniques - Zhyan A. Ahmed; Jehan M. Fattah Sheikh Suleimany (Polytechnic Journal)
Drought is among the most severe natural calamities induced by lack of water, having a negative implication on water resources and agriculture in the affected area. Drought types and severity vary by location, so understanding the spatial distribution can aid in developing measures to overcome this natural hazard. In this study, the areas vulnerable to droughts in the Mandawa watershed in the Kurdistan region of Iraq were determined by employing seven associated factors: rainfall, temperature, LULC, surfaceslope, soil texture, elevation, and distance to rivers. Satellite imagery of Landsat 8 OLI for 2021was employed to create the Land Use and Land Cover (LULC) and distance to rivers maps. The elevation and surface slope maps have been generated from the Digital Elevation Modelat 30 m resolution, soil texture map was extracted from The FAO Digital Soil Map of the Worldand the inverse distance weighting method was utilized to interpolate the rainfall and temperature throughout the watershed. Analytical Hierarchy Process (AHP)was used to create a pairwise compression matrix to obtain the weight of each parameter. In the Geographic Information System (GIS)environment, the combined impact of affecting factors was utilized to create the area's drought zonation map. The results indicated that only 5.2% and 13.8% of the study area is vulnerable to extreme and severe droughts, respectively. While more than 35% of the watershed is hardly vulnerable to droughts.